Antioxidant activity of Tween-20 and Tween-80 evaluated through different in-vitro tests. (31st December 2014) - Pérez-Rosés, Renato; Risco, Ester; Vila, Roser; Peñalver, Pedro; Cañigueral, Salvador
Abstract: Objectives: This study aimed to evaluate the possible antioxidant activity of Tween-20 and Tween-80, two amphipathic nonionic surfactants commonly used as solubilizers and stabilizers, whose pharmacological effects have been ignored to a large degree. Methods: Antioxidant activity was investigated in vitro measuring the scavenging activity on the stable free radical 2, 2-diphenyl-1-picrylhydrazyl (DPPH ● ), the production of reactive oxygen species (ROS) in activated human neutrophils using flow cytometry and the myeloperoxidase (MPO) inhibitory activity. Key findings: Tween-20 and Tween-80 did not show scavenging activity on DPPH ●, while produced a decrease of the ROS production in human neutrophils, being Tween-20 more active than Tween-80. Moreover, Tween-80 and Tween-20 were found to significantly stimulate MPO enzymatic activity. Conclusions: Our findings raise concerns with regard to the indiscriminate use of Tween-20 and Tween-80 in clinical and laboratory testing, since they could influence the results that are assigned to the tested substance.